Perancangan Sistem Kontrol Motor 3 Phase Pada Alat Bantu Pemasangan Material Roll Ply - Fikri, Gilang Ardiyanto; Prasetyo, Teguh (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
The increasing demand for tubeless tires from consumers makes the production capacity of the machines involved must be increased. Some of the things that become a problem are regarding the installation time of the material using several methods so that there are variations in the methods used in the material installation process. There are risks from each method used, starting from health reasons and also the productivity of the machine itself. After conducting a 4M analysis, we found a problem point in the method section, namely during the process of installing the ply material. Therefore, the purpose of this study is to design a construction tool for installing roll ply material, design a 3-phase motor control system, analyze the effect of having a tool for installing roll ply material on the productivity of BTU. The method used by researchers is PDCA as a determinant of the root causes of problems. REBA method for ergonomic analysis of employee work postures when installing ply material. The SMED method is used to analyze work steps that have no use value to the production proces.